The new treason of the intellectuals : can the university survive? - Docherty, Thomas, 1955- (Manchester : Manchester University Press, 2018)
This book delivers a damning criticism of the contemporary University system. It argues that the University has become politicised - that its primary purpose has shifted from education to the advancement of market-fundamentalist capital, an ideology that paints society as a war of all against all for individual financial gain. Against this, the book calls for a reconfiguration of the purpose of the University. It evokes the institution's wider ambitions and purposes: extending the range of human possibilities, seeking global justice and promoting democracy. Nothing less than ecological and human survival is at stake. Written by a senior academic and leading opponent of the modern University regime, this book exposes a troubling present while remaining optimistic for the future.
Online resource; title from PDF title page (EBSCO, viewed August 10, 2018).
Includes bibliographical references and index.
JSTOR
Keywords: Education, Higher -- Aims and objectives; Universities and colleges; College teachers; Universities; Enseignement supérieur -- Finalités.; Universités.; EDUCATION -- Higher; EDUCATION -- Philosophy & Social Aspects; College teachers; Education, Higher -- Aims and objectives; Universities and colleges